Choices with childbirth (Albron, Queensland Australia : Vacca Research, 1997)
Choices with childbirth is a self-directed learning program designed for health care professionals who advise and assist women during childbirth
CD is available at Koleksi Media, Perpustakaan HUKM
Module 1 : Progress labour and vacuum extraction
System requirements : Minimum PC-Compatible Configuration; 386SX at 20 MHz, 4 MB RAM, 6 MB hard disk space available, 2x CD-ROM drive, SVGA or better display card, mouse or similar input divice, Windows 3.1, Windows for Workgroups 3.11, Windows 95 or Windows NT 3.51 or later
System requirements : Minimum Macintosh Configuration; 68030 at 25MHz, 4 MB RAM available, 6 MB hard disk space available, 2x CD-ROM drive, 13' colour display, system software 7.0 or later
Keywords: Labor; Vacuum Extraction, Obstetrical